Another side of the association between body mass index (BMI) and clinical outcomes of cancer patients receiving programmed cell death protein-1 (PD-1)/ Programmed cell death-ligand 1 (PD-L1) checkpoint inhibitors: A multicentre analysis of immune-related adverse events. (March 2020) - Cortellini, Alessio; Bersanelli, Melissa; Santini, Daniele; Buti, Sebastiano; Tiseo, Marcello; Cannita, Katia; Perrone, Fabiana; Giusti, Raffaele; De Tursi, Michele; Zoratto, Federica; Marconcini, Riccardo; Russano, Marco; et al.
Abstract: Background: Several studies have found an association between higher body mass index (BMI) and improved clinical outcomes in cancer patients receiving programmed cell death protein-1 (PD-1)/programmed cell death-ligand 1 (PD-L1) checkpoint inhibitors. In a previous study, we found that overweight/obese patients were significantly more likely to experience any grade immune-related adverse events (irAEs) compared to non-overweight patients. Patients and methods: We conducted a 'real-life', multi centre, retrospective observational study aimed at comparing the incidence of irAEs among cancer patients treated with PD-1/PD-L1 inhibitors according to baseline BMI. Results: One thousand and seventy advanced cancer patients were evaluated. The median age was 68 years (range: 21–92), male/female ratio was 724/346. Primary tumours were: non-small-cell lung carcinoma (NSCLC) (653 patients), melanoma (233 patients), renal cell carcinoma (RCC) (152 patients) and others (29 patients). Median BMI was 25 (13.6–46.6); according to World Health Organisation (WHO) classification, 44 patients (4.1%) were defined as underweight, 480 patients (44.9%) as having a normal weight, 416 patients (38.9%) as overweight and 130 patients (12.1%) as obese. Higher BMI was significantly related to higher occurrence of any grade immune-related adverse events [irAEs] ( p < 0.0001), G3/G4 irAEs ( p < 0.0001) and irAEs leading to discontinuation (LTD) ( p < 0.0001). Overweight and obesity were confirmed predictors for irAEs of any grade at both univariate and multivariate analysis. The adjusted odds ratios (ORs) (compared to normal-weight) were 10.6; 95% confidence interval (95%CI): 7.5–14.9 for overweight, and 16.6 (95%CI: 10.3–26.7) for obese patients. Obesity was the only factor significantly related to a higher incidence of G3/G4 irAEs (OR = 11.9 [95%CI: 6.4–22.3], p < 0.0001) and LTD irAEs (OR = 8.8 [95%CI: 4.3–18.2], p < 0.0001). Overweight and obese patients experienced a significantly higher occurrence of cutaneous, endocrine, gastro-intestinal (GI), hepatic and 'others' irAEs, compared to normal-weight patients. Only obese patients experienced a significantly higher occurrence of pulmonary and rheumatic irAEs, compared to normal-weight patients. Conclusions: Considering the previously evidenced association between higher BMI and better outcome, the current finding about the relationship between BMI and irAEs occurrence can contribute to consideration of these findings as the upside of the downside, which underlies an 'immunogenic phenotype'. Highlights: Several studies have found an association between higher BMI and improved outcomes in patients receiving PD-1/PD-L1 checkpoint inhibitors. The upside of the downside of this obesity paradox, might be the association between BMI and immune-related adverse events (irAEs). In this large case series, we found a significant association, between BMI and irAEs.